PREDICTING THE BIODEGRADABILITY NATURE OF IMIDAZOLE AND ITS DERIVATIVES BY MODULATING TWO HISTIDINE DEGRADATION ENZYMES (UROCANASE AND FORMIMINOGLUTAMASE) ACTIVITIES - Veeraragavan, Vijayakumar; Narayanaswamy, Radhakrishnan; Chidambaram, Rameshkumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The biodegradation pathway of substituted imidazole ring compounds has been reported to have close analogy to the histidine degradation pathway. This prompted the present study to be carried out on 12 selected imidazole and its derivatives which are 1-imidazole, 1, 2-dimethylimidazole, 1-ethyl imidazole, 2-ethyl-4-methylimidazole, 2-isopropylimidazole, 2-Isopropyl-4-nitro-1H-imidazole, 1-methylimidazole, 2-methyl-5-nitroimidazole, 2-methyl-1-vinylimidazole, 1-nitro imidazole, 1-phenyl imidazole, and 1-vinylimidazole. Methods: The imidazole and its derivatives were evaluated on the docking behavior of urocanase and formiminoglutamase using PatchDock. In addition, molecular physicochemical, drug-likeness, absorption, distribution, metabolism, and excretion analyses (ADME) were done. Results: The molecular physicochemical analysis revealed that all the tested ligands showed nil violation and complied well with the Lipinski's rule of five. ADME analysis showed that 1-phenylimidazole alone predicated to have cytochrome P450 1A2 inhibition effect. Docking studies revealed that 1-nitroimidazole showed the least atomic contact energy with both targeted enzymes (urocanase and FIGase). Conclusion: Inhibition of both enzymes (urocanase and FIGase) might show poor biodegradability nature. Thus, we can predict biodegradability nature of imidazloe and its derivatives by modulating two histidine degradation enzymes activities.